1999
DOI: 10.1111/j.1574-695x.1999.tb01713.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cigarette smoke on adherence of respiratory pathogens to buccal epithelial cells

Abstract: Smoking is associated with an increased risk of respiratory tract infection in adults. In children, exposure to cigarette smoke is a risk factor for respiratory tract infection and bacterial meningitis: Active smoking and passive exposure to cigarette smoke is also associated with carriage of some potentially pathogenic species of bacteria in both adults and children. The aims of the study were to determine the effect of active smoking on: (1) bacterial binding to epithelial cells; (2) expression of host cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 21 publications
1
63
0
2
Order By: Relevance
“…Interestingly, smoking cessation is associated with a reversion to the microflora found in never-smokers, thereby suggesting that cigarette smoke does indeed favour colonisation by pathogens [57]. Supporting this notion, cigarette smoke enhances bacterial attachment to epithelial cells and promotes changes in virulence by modifying bacterial gene expression [58][59][60].…”
Section: Effect Of Cigarette Smoke Exposure On Bacterial Infectionsmentioning
confidence: 53%
“…Interestingly, smoking cessation is associated with a reversion to the microflora found in never-smokers, thereby suggesting that cigarette smoke does indeed favour colonisation by pathogens [57]. Supporting this notion, cigarette smoke enhances bacterial attachment to epithelial cells and promotes changes in virulence by modifying bacterial gene expression [58][59][60].…”
Section: Effect Of Cigarette Smoke Exposure On Bacterial Infectionsmentioning
confidence: 53%
“…In general, it was found that microorganisms adhere more to (buccal) epithelial cells isolated from patients who either have a chronic disease or smoke (6,19) and to infected human epithelial (HEp-2) cell lines (20) than to cells from healthy control subjects or noninfected cell lines. The same increase has been described in studies on vaginal, buccal, uroepithelial, and periurethral cells isolated from patients (children, girls, and women) with recurrent UTIs (5,21,22).…”
Section: Secretor Statusmentioning
confidence: 99%
“…Relationships between diseases and the adherence of microorganisms to patient cells have been investigated before (6,19,20). In general, it was found that microorganisms adhere more to (buccal) epithelial cells isolated from patients who either have a chronic disease or smoke (6,19) and to infected human epithelial (HEp-2) cell lines (20) than to cells from healthy control subjects or noninfected cell lines.…”
Section: Secretor Statusmentioning
confidence: 99%
“…For all studies, the adherence of bacteria to buccal cells (see Fig. 1D) was established with the use of a conventional white-light microscope (37,42,50).…”
Section: Gudakhu Yesmentioning
confidence: 99%